América Latina y la segunda UNCTAD - Baltra Cortés, Alberto (Estudios Internacionales, 1969)
The Latin American point of view on the results of UNCTAD II cannot be fully understood without taking a look at the nature of the profound structural crisis that Latin America has been experiencing for some years. In the midst of this gloomy outlook, UNCTAD I opened a horizon of hopes that were not satisfied. And then, the results of UNCTAD II were of very limited scope and, in some aspects, there was even a notable setback in relation to what was agreed in Geneva in 1964, a fact that generated disappointment and frustration in this region. However, it is possible to draw some positive lessons, such as the reaffirmation of the idea that Latin America needs to increase its bargaining power.